Ecotoxicity Studies for On-Site Disposal of Decant Water During Oil Spills: A Review - Liu, Bo; Chen, Bing; Ling, Jingjing; Ye, Xudong; Dong, Guihua; Matchinski, Ethan James; Zhang, Baiyu (Frontiers in Environmental Science, 2022)
Mechanical oil recovery, a most used tool for oil spill response, can generate a considerable proportion of oil-contaminated water (10% ~ 70%). Large storage space is commonly required to transport the recovered oil and water mixture to shore. Transit and transportation consume loads of time, money and resources while reducing oil recovery's overall efficiency and capacity. Techniques of on-site treatment and disposal of oily wastewater provide benefits for oil recovery by freeing storage space. However, the high petroleum content of decant water can lead to uncertain risks, if discharged into the marine ecosystem. Insufficient ecological toxicity data and research limit the standardization and establishment of regulative tools. To fill the knowledge gaps, this review comprehensively summarized recent studies on the potential impacts of the organic composition of decanting water, including oil water accommodated fractions, dispersed oil droplets, and other related chemicals, on various marine species (i.e., bacterium, invertebrates, fishes, plants, reptiles, and mammals). The toxicity effects and the ecological endpoints of oils, TPH, and PAHs to different species were discussed. Recommendations for future studies on the ecological impacts and the decant water composition were provided to support the on-site disposal of the water fraction.